My Highland rogue - Ranney, Karen (Ranney, Karen. Highland fling, 2020)
"Since she was a little girl, Jennifer Adaire, daughter of the earl of Burfield, has loved Gordon McDonnell, even though his station as the gardener's son made him strictly forbidden to her. After Gordon was forced from Adaire Hall, taking Jennifer's heart with him, he headed for London, intent on making a better life for himself. Though they've kept in touch through letters and Jennifer has waited patiently for him, it's taken Gordon five years to return to Scotland. Now, Jennifer doesn't know if she can manage seeing again the man she loves--but can never have. In the time since his departure, Gordon has achieved the success he's always sought. When he learns that his father is dying, he returns home and discovers much to his surprise that the feelings he's always had for Jennifer burn ever stronger. But when a family secret surfaces, Jennifer and Gordon's chance at a future together could be threatened..."--Provided by publisher.